Competition for International Students - Green, Madeleine; Koch, Kim (International Higher Education, 2010)
The competition for recruitment of international students is heating up. In the United States, the efforts are mostly done by each institution. In the United Kingdom, the Prime Minister launched the initiatives and set the target. Germany focuses on a regional recruitment from other European countries. In France, the government put agencies in many countries to offer support for application and events for promotion. Australia began a recruitment campaign for six key markets in Asia. Other areas also set strategies and goals for attracting international students.